Synthesis and characterization of cu2-xs structures by different chemical routes for electronic applications - Lima, João V.M. [UNESP]; Silva, Rafael A. [UNESP]; Santos, Stevan B.O. [UNESP]; Graeff, Carlos F.O. [UNESP]; Scalvi, Luis V.A. [UNESP] (FapUNIFESP (SciELO), 2021)
Copper sulfides are materials with different technological applications due to different possibilities of phases, which result in different properties. Thus, obtaining particles with different stoichiometry of the materials is of great interest. Two simple chemical routes were used to obtain copper sulfides (Cu2-xS) particles of different phases and stoichiometry. One of the obtained powders was used for thin film deposition through resistive evaporation and characterized. From scanning electron microscopy the particle size was found as around 500 nm. The second route leads to non-stoichiometric powder with characteristic CuS, Cu9S5 and Cu2S planes detected in the XRD diffractograms. Thin films from this route were also obtained by resistive evaporation. The amorphous film obtained after evaporation was submitted to thermal annealing at 200 ° C/2h, becoming semi-crystalline. The deposited film showed good adhesion to the substrate and low roughness, in addition to a bandgap of 2.5 ± 0.1 eV and a resistivity of 1x10-2 Ω.cm, values in good agreement with those reported in the literature. The techniques used here proved to be of good quality for deposition of copper sulfide films, and can be used as a simpler alternative in addition to commonly used for deposition of copper sulfide films.
Keywords: Chemical Routes; Copper Sulfide; Resistive Evaporation